Influence of selected strategic variables on the development of the intellectual capital of an enterprise = Wpływ wybranych zmiennych o charakterze strategicznym na rozwój kapitału intelektualnego przedsiębiorstwa - Prusak, Rafał (Zielona Góra: Faculty of Economics and Management Press)
Intellectual capital is an important issue of currently undertaken studies in the field of enterprise organization and management. The introduction of this concept has undoubtedly opened up new prospects for enterprises to perceive their business activity and building market advantages. At the same time, however, it has given rise to many new problems associated with the hard-todetermine nature of intellectual capital and its internal and external relationships and dependencies. An attempt has been made in the article to analyze problems related to the dissemination of the concept of intellectual capital, and its practical use, and to assess the state of the intellectual capital components in the surveyed entities.
Keywords: kapitał intelektualny; zarządzanie kapitałem ludzkim; Zarządzanie strategiczne; Intellectual capital; human capital management; Strategic management